Social media network size and semantic networks for collaboration in design. (1st January 2012) - Danowski, James A.
Social media are fundamentally based on communication networks containing friends, acquaintances, or others. Because communication is essential to collaboration on activities, we assume that those who have more contacts in work-oriented social media are more likely to be collaborative in their work behaviours. Design educators have been stressing of importance of collaboration in training recent cohorts of design students. Our goal was to empirically examine designers on the LinkedIn social media site in terms of how they describe collaboration and why. The results supported hypotheses that designers with larger networks of online contacts were more verbal, had higher collaborative word use, were more positive, were more evaluative, used more competence-oriented words, and had semantic networks for collaboration that were more complex, with greater discrimination, differentiation, and integration. Given the experiences of current young adults with social media, we further hypothesise that future design work will become increasingly collaborative.